A simplified Von Neumann method for linear stability analysis - Shi, Jian (Cranfield University, 1993)
This paper investigates the issue of linear stability analysis for two and three level explicit and implicit one dimensional finite different numerical schemes. A new approach which simplifies the Von Neumann method is presented. It has been proved that the new technique is efficient and effective for linear stability study. This is especially true for high-order and complicated numerical schemes.